Hybrid radiation modeling for multi-phase solar-thermal reactor systems operated at high-temperature. (15th December 2016) - Groehn, Arto J.; Lewandowski, Allan; Yang, Ronggui; Weimer, Alan W.
Highlights: Interfacing of ray-tracing and finite-volume radiation models at an arbitrary surface. Validation of the coupling method by comparison with full ray-tracing simulations. Effect of tube radius on ceria reduction efficiency in solar-thermal reactors. Abstract: This work presents a method to couple ray-tracing and finite-volume radiation models at an arbitrary surface via both spatial and angular discretization. The interfacing algorithm is validated by comparing its results with full ray-tracing simulations of a compound parabolic concentrator as well as a large-scale solar-thermal reactor. The validated model is employed to investigate effects of silicon carbide tube radius on efficiency of ceria particle reduction for such applications as water or carbon dioxide splitting. Decreasing reactor tube radius from 25 to 5 cm reduced the total oxygen vacancy production rate from 3.7 to 0.3 kmol/h but nearly doubled the extent of ceria conversion when the particle bed velocity was maintained.